Hidden Hitchcock - Miller, D. A. (The University of Chicago Press, 2016)
Intro -- Contents -- Preview -- Hidden Pictures (Strangers on a Train) -- Understyle (Rope) -- The Long Wrong Man -- Credits -- Notes -- Bibliography.
https://katalog.adlr.link/Record/0-1656252570